Cytology of Paediatric lesions: a tertiary care centre experience during COVID-19 - Balakrishnan, Padmapriya; Midhuna, Bhatta; Lahari, Pujari; Nandini, Jampa; Uma, Prasad; Atla, Bhagyalakshmi (International Journal of Research in Medical Sciences, 2021)
Background: Paediatric lesions are worrisome and need immediate attention with early diagnosis. Fine needle aspiration cytology (FNAC) is safe, cost effective, minimally invasive method which helps in diagnosis and guides for treatment of various paediatric lesions. Methods: This was an observational study done during the pandemic of COVID-19 at department of pathology in Andhra Medical College, Visakhapatnam from March 2020 to October 2020 .The total number of cases were 91 who underwent fine needle aspiration (FNA) during this period. USG guided aspiration and fluids are also included in the study. Slides were fixed in 95% isopropyl alcohol and stained with Haematoxylin and Eosin. May Grunwald Giemsa stain, CBNAAT for acid fast bacilli and correlation with histopathology was done wherever required and results were tabulated. Results: In the present study the lesions were more common in female children (68.13%) and in the age group of 11-15 years (35.16%).Benign lesions (80.91%) were more common than malignant lesions. Majority of benign lesions were reactive lymphadenitis (32.5%) followed by tuberculous lymphadenitis (23.75%). The common malignant lesions were lymphoblastic and Hodgkin’s lymphoma, metastatic nasopharyngeal carcinoma, malignant peripheral nerve sheath tumour (MPNST), Langerhans cell Histiocytosis and Ewing’s sarcoma. Conclusions: Extra pulmonary tuberculosis in children is highly variable in severity and rate of progression with long term sequelae. The spectrum of malignancies in children is variable and region based. FNAC helped in early diagnosis and management of these cases.